Influence of implant location on the clinical outcomes of implant abutments: a systematic review and meta-analysis - ElHoussiney AG; Zhang H; Song J; Ji P; Wang L; Yang S (Dove Medical Press, 2018)
Amr G ElHoussiney,1 He Zhang,2 Jinlin Song,2 Ping Ji,2 Lu Wang,1 Sheng Yang1 1Department of Prosthodontics, 2Chongqing Key Laboratory of Oral Diseases and Biomedical Sciences, Chongqing Municipal Key Laboratory of Oral Biomedical Engineering of Higher Education, College of Stomatology, Chongqing Medical University, Chongqing, China Purpose: To compare the failure events and incidence of complications of different abutment materials in anterior and posterior regions. Failure was defined as complete loss of the abutment requiring replacement by a new abutment.Materials and methods: Electronic searches using PubMed/Medline and Google Scholar complemented with manual searches were performed with specific search terms. Searches were restricted to publications in English between January 2006 and March 2016.Results: A total of 863 and 1,264 implants were inserted in the anterior and posterior regions, respectively, in a total of 1,529 patients. No titanium abutments failed in anterior or posterior regions. On the other hand, 1.6% of zirconia abutments failed in the anterior region and 1.5% failed in the posterior region. Technical complications occurred mostly in the posterior region and mostly involved zirconia abutment. Meta-analysis was possible only for zirconia-abutment failure, due to considerable heterogeneity of studies and outcome variables. No significant difference in failure rate was found between anterior and posterior zirconia abutments (risk ratio 1.53, 95% CI 0.49–4.77; P=0.47).Conclusion: This systematic review and meta-analysis showed similar outcomes of different abutment materials when used in anterior and posterior regions in terms of failure events and biological and aesthetic complications. The only significant finding was the increased incidence of technical complications in the posterior region, mostly involving zirconia abutments. Abutment-screw loosening was the most common technical complication. Keywords: implant abutment, zirconia, titanium, implant location, systematic review